(untitled) (Sociologisk Forskning, 2018)
Public safety in Sweden. A study of a crime policy symbol Public safety has become an increasingly important part of crime policy debates in the Western countries. In Sweden, the concepts of trygghet (safety) and its negative counterpart otrygghet (insecurity) are often used in discussions about public safety and fear of crime. In this article, I argue that in order to understand Swedish crime policy, the symbolic meaning of these concepts cannot be overlooked. The political debates on public safety preceding the general elections in 2006, 2010 and 2014 are analysed with reference to three political parties: the Social Democratic party, the Conservative Party (Moderaterna) and the Sweden Democrats. By analysing the concept of safety (trygghet) as a condensation symbol, with its imaginative potential stemming from the historically strong relation between safety and the welfare state, this article illustrates how political solutions within the crime policy field are depicted as benign and universal. The article further explores how the political usage of the concept of safety generates feelings of ”national pride” to the general public.